Prevalence of Minor β-thalassemia Based on RBC Indices among Final Suspected Individuals in Premarital Screening Program Referred to Genetic Laboratories - Alireza Moafi; Sadeg Valian; Zahra Nikyar; Mehrdad Zeinalian; Maryam Momenzadeh; Soheila Rahgozar (International Journal of Hematology-Oncology and Stem Cell Research, 2010)
"nAbstract "nIntroduction: The current study evaluated the value of red blood cell (RBC) indices and the corresponding cut- off points for β-thalassemia control programs in Iran. "nMaterials and Methods: 1,150 individuals (575 couples) with low RBC indices and normal hemoglobin A2 who had been referred to the Genetic Centre of Isfahan, were tested during pre-marital screening analyses, in the 2 year period, 2006-2008. β-thalassemia mutations were evaluated. "nResults: β-thalassemia was identified in 67.8% of the cases with both mean corpuscular volume (MCV) less than 78fl and mean corpuscular hemoglobin (MCH) less than 26 pg. However, 4.1% of the individuals with "n78≤ MCV≤ 80 tested positive for thalassemia. MCV showed a higher diagnostic reliability than MCH. However, the accompaniment of MCH<26 with MCV<78 increased the risk of thalassemia 35 times. A significant association was found between the prevalence of minor β-thalassemia and educational levels, race and familial relationships. "nConclusion: According to the results of this study, it seems that MCV=80fl can be used as a proper cut- off point for the screening of minor β-thalassemia. Although in the present study MCV was found to have a higher diagnostic reliability than MCH, MCH <26 along with MCV are very helpful indices for the counselor physician to estimate the risk of minor β-thalassemia more accurately. "n "nKey words: Minor β-Thalassemia, Screening, MCH, MCV, Thalassemia Preventing Program,